2020
DOI: 10.3389/fpls.2020.00287
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Dietary Diary of Bumble Bee

Abstract: Bumble bees are important crop pollinators and provide important pollination services to their respective ecosystems. Their pollen diet and thus food preferences can be characterized through nucleic acid sequence analysis. We present ITS2 amplicon sequence data from pollen collected by bumble bees. The pollen was collected from six different bumble bee colonies that were placed in independent agricultural landscapes. We compared next-generation (Illumina), i.e., short-read, and thirdgeneration (Nanopore), i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Our results can contribute to ongoing discussions that apply and test different methods to quantify pollen grain counts (Baksay et al., 2020; Pornon et al., 2016). Given the growing interest in both microscopic (Gallardo‐Caballero et al., 2019) and molecular (Baksay et al., 2020; Leidenfrost et al., 2020) pollen analyses for pollen identification and quantification, our study highlights that the methods should be chosen carefully and in a targeted manner.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results can contribute to ongoing discussions that apply and test different methods to quantify pollen grain counts (Baksay et al., 2020; Pornon et al., 2016). Given the growing interest in both microscopic (Gallardo‐Caballero et al., 2019) and molecular (Baksay et al., 2020; Leidenfrost et al., 2020) pollen analyses for pollen identification and quantification, our study highlights that the methods should be chosen carefully and in a targeted manner.…”
Section: Discussionmentioning
confidence: 97%
“…New developments in microscopic pollen detection using deep learning techniques (Gallardo‐Caballero et al., 2019) or in full‐length amplicon or genome sequencing with, for example, nanopore sequencing techniques (Lang et al . 2019; Leidenfrost et al., 2020; Peel et al., 2019) could improve the weaknesses of both approaches (e.g., time expenditure in microscopy or quantification accuracy in molecular methods). However, studies are needed to compare and evaluate the accuracy of those new developments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar spillover processes have been observed from mango (Simba et al., 2018) or OSR (Kovacs‐Hostyanszki et al., 2013) to natural vegetation. Both crops, OSR and strawberry, can provide pollen and nectar as a reward (Bänsch, Tscharntke, Ratnieks, et al., 2020; Knopper et al., 2016; Leidenfrost et al., 2020). It has been shown that the attractiveness of OSR to honey bees and some solitary bee species is higher than the attractiveness of strawberry while the attractiveness of both crops to bumble bees is similar (Knopper et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar spillover processes have been observed from mango (Simba et al, 2018) or OSR (Kovacs-Hostyanszki et al, 2013) to natural vegetation. Both crops, OSR and strawberry, can provide pollen and nectar as a reward (Bänsch, Tscharntke, Ratnieks, et al, 2020;Knopper et al, 2016;Leidenfrost et al, 2020).…”
Section: Discussionmentioning
confidence: 99%